Finance and the World Economy in Weimar Cinema - Lyons, Owen (Film culture in transition., 2023)
Between the World Wars, the contours of what would come to be understood as the world economy began to appear on in the cinemas of the Weimar Republic. To a non-specialist audience, it remained an invisible and barely understood effect on everyday life. Finance and the World Economy in Weimar Cinema argues that the popular understanding of this newly interconnected financial world order, and its new inhabitants, is essential to an understanding of the cultural products of the Weimar Republic - particularly in relation to ideas of gender, nation and modernity. This popular depiction of finance capital appears everywhere in 1920s Germany but has been overlooked, particularly in the films of the time. As a visual record, these films reveal the stock exchange as an essential space of modernity and coincide with the beginning of the abstraction of financial markets that would result in their increasing propagation as images and as a vast labour of representation throughout the twentieth century.